1989
DOI: 10.1159/000111898
|View full text |Cite
|
Sign up to set email alerts
|

The Cholinergic System in Developing Cerebellum: Comparative Study of Normal, Hypothyroid and Underfed Rats

Abstract: To overcome the deficiencies of previous findings, the activities of choline acetyltransferase (ChAT) and acetylcholinesterase (AchE) were studied at very short age intervals to allow a more precise definition of the shape and timing of their developmental curves in normal, hypothyroid and underfed rats. In addition, AchE expression in developing cerebellum was studied histochemically in these three neurological models. When compared with structural findings in the literature, the results provide the following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 37 publications
2
19
0
Order By: Relevance
“…The abundance of cholinergic synthetic enzymes during the long cerebellar maturative process (Clos et al., 1989) supports this assertion. More specifically, experimental studies have demonstrated that the dynamic sequence of morphological steps that regularly occur during CC development, mainly consisting in a progressive thinning until the disappearance of the EGL due to cell death or cell migration in the IGL, coincide with the maturation of the cholinergic system (Clos et al., 1989; Court et al., 1995). The activation of the α7-nAChR subtype appears to be particularly involved in the maturation of the granule layers (Caruncho et al., 1997; Opanashuk et al., 2001; Prestori et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The abundance of cholinergic synthetic enzymes during the long cerebellar maturative process (Clos et al., 1989) supports this assertion. More specifically, experimental studies have demonstrated that the dynamic sequence of morphological steps that regularly occur during CC development, mainly consisting in a progressive thinning until the disappearance of the EGL due to cell death or cell migration in the IGL, coincide with the maturation of the cholinergic system (Clos et al., 1989; Court et al., 1995). The activation of the α7-nAChR subtype appears to be particularly involved in the maturation of the granule layers (Caruncho et al., 1997; Opanashuk et al., 2001; Prestori et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…during embryonic and early postnatal development (Clos et al 1989;Feller et al 1996;Milner and Landmesser 1999;Zoli et al 1995). These cholinergic properties are subsequently down-regulated at later developmental stages that coincide with the glutamatergic synapse formation and increased glutamate-dependent excitatory synaptic activity (Wong 1999).…”
Section: Functional Implicationsmentioning
confidence: 99%
“…1991), with particularly high levels of ACh and choline seen in neonatal cerebellum, resulting from a high ratio of ChAT to AChE activities (Kasa et al . 1982; Clos et al . 1989).…”
Section: Physiological and Clinical Implicationsmentioning
confidence: 99%